Pendampingan Pembuatan Produk Usaha BUIS (Bubuk Ikan Seluang) sebagai Bahan Tambahan pada Makanan untuk Mencegah Stunting - Rosmainar, Lilis; Yuliana, Yuliana; Wardhana, Vinsen Willi (Universitas Nusantara PGRI Kediri, 2025)
Stunting is defined as a disruption in a child's growth and development. The prevalence of stunting must be continuously reduced. Therefore, various efforts are being made, such as providing adequate nutrition. One food source that is high in protein and high in calcium is the seluang fish (Rasbora Argyrotaenia). The majority of residents living along the river in Palangka Raya earn their living as fishermen. This fish is widely found and sold in the market, making it quite affordable. To increase the market value of this fish, innovations have been made in processing seluang fish, namely by making seluang fish powder. The processing method involves boiling the fish in a pressure cooker, drying it in an oven, and then grinding it into a powder. The resulting fish powder is blackish in color and has a distinctive odor. Training on making fish powder was conducted for residents living along the river, attended by 30 residents, and the participants were very enthusiastic about the activity.